Comparative Analysis of the Head Loss of Two Centrifugal Pumps in a Fluid Test Laboratory - Ridho Choirul Anam; Edi Widodo; Iswanto; A’rasy Fahruddin (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this study was to determine the characteristics of the two centrifugal pumps using the same circuit and to obtain the resulting value, namely head, discharge, pump power, efficiency of the two pumps. And variations in valve opening settings used are full valve openings, valve openings 2/3, and valve openings 1/3 which have different coefficients at each valve opening. This research method was carried out experimentally. The fluid used is water, fluid pressure measurement using a pressure gauge to measure the pressure side (discharge) and a vacuum pressure gauge to measure the pressure which is relatively lower than the atmospheric pressure for the pump on the suction side (suction) and using a flow meter to determine the volume or discharge water used. The results of this centrifugal pump test equipment research found that the working pump shows that the resulting discharge affects the head value, pump power, and pump efficiency obtained, the higher the total head value, the smaller the resulting discharge. However, this centrifugal pump test equipment can be used for fluid practicum activities in the mechanical engineering department in the mechanical laboratory.